Modelo Conceptual para o Depuramento de Programas Distribuídos por Troca de Mensagens - Cláudio, Ana Paula (2003)
This dissertation presents a conceptual model of message-passing distributed programs that is used as a base for the debugging of this kind of programs. The model is independent from the message-passing software used and incorporates several facilities aimed at supporting debugging: generation of a space-time diagram which shows the progression of the execution being studied, detection of race conditions, detection of particular kinds of predicates and representation of causality cones. Conceived according to the object-oriented methodology, the model is composed of two groups of classes: kernel classes and graphical classes. The first group contains the classes which are models of the entities envolved in the execution. The classes in the second group, graphical classes, are subclasses of the previous ones and, additionaly, are responsible for drawing the space-time diagram. All the details that depend on the graphical software adopted are encapsulated in graphical classes. A tool called MPVisualizer implements the conceptual model. This tool contains a reexecution mechanism that allows the reproduction of behaviours exhibited in previous executions by programs that are potentially nondeterministic. The capability of reproducing behaviours is vital in cyclic debugging, a frequently used technique in the debugging of sequencial programs